2011
DOI: 10.1080/12297119.2011.9711015
|View full text |Cite
|
Sign up to set email alerts
|

Latent Factors of Executional Elements Influencing Commercial Likeability: An Exploratory Study of Super Bowl Commercials

Abstract: Academic researchers have focused very little on television advertising execution since the mid-1990s despite the fact that television remains one of the most powerful media in advertising. This study try to fill this gap by investigating the executional elements adopted in recent television commercials, while attempting to resolve some of the weaknesses found in the prior research. Prior research in advertising execution has predominantly focused on analyzing the presence or absence of individual executional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The observation that the effect of Super Bowl advertising does not manifest itself in the same way under varying levels of product involvement is consistent with previous studies. For example, Kim and Cheong [45] found that the influences of latent factors in Super Bowl commercials (i.e., female, affective, time-elapse, divergent, and music factors) on ad likability were greater when the advertised product was a low-rather than high-involvement product. It may be that the advantage of Super Bowl advertising is most beneficial for low-involvement product categories.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the effect of Super Bowl advertising does not manifest itself in the same way under varying levels of product involvement is consistent with previous studies. For example, Kim and Cheong [45] found that the influences of latent factors in Super Bowl commercials (i.e., female, affective, time-elapse, divergent, and music factors) on ad likability were greater when the advertised product was a low-rather than high-involvement product. It may be that the advantage of Super Bowl advertising is most beneficial for low-involvement product categories.…”
Section: Discussionmentioning
confidence: 99%
“…On the Monday after the Super Bowl, USA Today publishes the Ad Meter scores. These scores have the advantage of ecological validity, in contrast to the measures typically used in laboratory environments (Kim & Cheong 2011a, 2011b. Just as the average Super Bowl viewer watches advertisements during the game, these volunteers evaluate actual commercials in real time during the telecast.…”
Section: Sample Commercialsmentioning
confidence: 99%
“…Consequently, previous studies on Super Bowl advertising have used these Ad Meter scores to measure attitudes towards Super TV sport and embedded advertising Bowl commercials (e.g. Kelley & Turley, 2004;Kim & Cheong 2011a, 2011bKim & Morrison, 2003;Tomkovick et al, 2001).…”
Section: Sample Commercialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased partnerships between the sport industry and the media have led to a significant increase in sport advertising in both the traditional and modern media (Kim and Cheong, 2011). For instance, in the United States, companies spent $34.9 bn annually on sport IJSMS 22,4…”
Section: Introductionmentioning
confidence: 99%